1999
DOI: 10.1042/bj3440185
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of plant sulpholipid labelling from UDP-[14C]glucose in pea chloroplasts

Abstract: The sulphoquinovosyldiacylglycerol (sulpholipid) zone obtained by TLC of pea chloroplast lipids yields, on hydrolysis, not only sulphoquinovose but also galactose and glucose. Following incorporation from UDP-["%C]glucose, the percentages of the total radioactivity in these three sugars were typically 1, 5 and 85 %, respectively. The occurrence of the glucolipid causes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…UDP-Glc for SQDG biosynthesis has also been speculated to be of cytosolic origin, and certain proteins have been proposed as the candidate transporters of UDP-Glc for SQDG biosynthesis (Knappe et al, 2003). However, a feeding experiment in which radiolabeled UDP-Glc was applied to isolated chloroplasts of the pea revealed that radioactivity was not efficiently incorporated into the sulfoquinovose moiety (Roy and Harwood, 1999), raising the question of how UDP-Glc is transported to the chloroplasts. This study revealed that UDPGlc for SQDG biosynthesis is generated in the chloroplasts by the UGP3 protein, not incorporated from extrachloroplastic space ( Figure 9).…”
Section: Udp-glc For Sqdg Synthesis Is Generated Inside Chloroplasts mentioning
confidence: 93%
“…UDP-Glc for SQDG biosynthesis has also been speculated to be of cytosolic origin, and certain proteins have been proposed as the candidate transporters of UDP-Glc for SQDG biosynthesis (Knappe et al, 2003). However, a feeding experiment in which radiolabeled UDP-Glc was applied to isolated chloroplasts of the pea revealed that radioactivity was not efficiently incorporated into the sulfoquinovose moiety (Roy and Harwood, 1999), raising the question of how UDP-Glc is transported to the chloroplasts. This study revealed that UDPGlc for SQDG biosynthesis is generated in the chloroplasts by the UGP3 protein, not incorporated from extrachloroplastic space ( Figure 9).…”
Section: Udp-glc For Sqdg Synthesis Is Generated Inside Chloroplasts mentioning
confidence: 93%